Keamanan dan Keselamatan Implementasi Internet of Things (IoT): Tantangan pada Sektor Industri dan Rumah Tangga - Muhammad Tengku Sadewa; Tata Sutabri (Jurnal Kendali Teknik dan Sains, 2026)
The development of the Internet of Things (IoT) has brought significant changes to various sectors of life, particularly in industrial and household environments. IoT refers to a network of interconnected devices that are capable of collecting, transmitting, and exchanging data through the internet, thereby enabling automated monitoring and control. This technology offers considerable potential to improve operational efficiency, convenience, security, and safety. In the industrial sector, IoT supports real-time monitoring, predictive maintenance, production optimization, and more effective resource management. In households, IoT enables the use of smart devices that can improve comfort, energy efficiency, and home security. Nevertheless, the implementation of IoT still faces several challenges, including data security risks, privacy concerns, limited infrastructure, interoperability issues, high implementation costs, and low levels of digital literacy. This study employs a phenomenological approach to understand the implementation of IoT and the challenges associated with its information and communication technology. The findings are expected to provide a comprehensive overview of how IoT is adopted in industrial and household settings, as well as identify the technological and social barriers that must be addressed to support its sustainable development.